Analysis of the Effect of Economic Growth, Population, and Open Unemployment Rate on the Human Development Index in the Tapal Kuda Region of East Java - Maharani, Tiara; Primandhana , Wiwin Priana (Indonesian Journal Publisher, 2025)
This study examines the influence of economic growth, population size, and open unemployment rate on the Human Development Index (HDI) in the Tapal Kuda region of East Java, which includes the districts of Banyuwangi, Bondowoso, Jember, Lumajang, Probolinggo, Pasuruan, and Situbondo during the period 2014–2023. The analysis was conducted using secondary data from the Central Statistics Agency (BPS) employing panel data regression via the Fixed Effects Model (FEM) approach. The findings indicate that economic growth does not have a significant negative impact on the HDI, suggesting that changes in economic growth have not yet notably improved or reduced the quality of life for residents in this region. The population size variable has a significant positive impact, indicating that population growth is accompanied by improved access to education, health services, and living standards. Conversely, the open unemployment rate has a significant negative impact on the HDI, indicating that high unemployment is a barrier to human development progress. Based on these findings, policies that prioritize equitable development, job creation, and improvements in the quality of education and health services are needed to accelerate HDI improvement in the Tapal Kuda region.